Family in Top Management Team and Firm Value: Do Gender and Education of Family Manager Matter? - Hadi Sumarsono (Shirkah: Journal of Economics and Business, 2020)
The in-hand study sheds some light on empirical relationship between involvement of family members in the top management team and family firm value. Specifically, this study examines how gender and education of family managers affect firm value in Indonesian context. The total sample employed in this study consisted of 935 observations with 235 family companies. The data required in this study were collected from various sources. Drawing on fixed effect regression, the results identified that the involvement of family members in top management team significantly affected the family firm value. It was also revealed that the female family manager had a lower firm value than the male family manager. Moreover, the education level of the family manager positively affected the firm value. These results provide an empirical evidence on how gender and education of family managers influence family firm value. It is further depicted that the results of this study are in line with the upper echelons theory in which the differences in human resources (e.g. gender and education) arisen from the family involvement in a management undeniably affect family firm value. As for the practical contribution, this study suggests that powerful actors in the family firms should be a family member involved in a management. It is also a worth saying that the involvement of family members on the top management teams should consider gender and level of education.